2006
DOI: 10.2139/ssrn.1007043
|View full text |Cite
|
Sign up to set email alerts
|

Do Mergers Create or Destroy Value? Evidence from Unsuccessful Mergers

Abstract: ABSTRACT:In this study, we examine unsuccessful takeover attempts for new evidence on whether mergers create or destroy value for acquirers and targets. We contribute to the literature in three important areas. First, we contribute to the literature on signaling by investigating whether a takeover attempt signals investors about the quality of firm management as well as the quality of the specific firm investment under consideration. We find that bid announcement returns are partially, but not completely, reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…where NI -net income as stated in income statement at the end of the year; аverage total assets -average total assets over the year as stated in balance sheet . This approach does not allow to take a closer look at the changes in the financial performance of the firms after the acquisition, but it gives an opportunity to take into account the possible effects of financial synergy arising between organizations [Cole, Vu, 2006] . G .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…where NI -net income as stated in income statement at the end of the year; аverage total assets -average total assets over the year as stated in balance sheet . This approach does not allow to take a closer look at the changes in the financial performance of the firms after the acquisition, but it gives an opportunity to take into account the possible effects of financial synergy arising between organizations [Cole, Vu, 2006] . G .…”
Section: Methodsmentioning
confidence: 99%
“…Another motive to conduct an acquisition is a synergy effect that happens after M&A deals as a result of sharing knowledge and resources between organizations . According to [Cole, Vu, 2006], mergers and acquisitions can create value by making operating synergies that can happen in the form of economies of scale or economies of scope . The researchers state that economies of scale have the highest chances to be realized when companies operate in the same line of business Target's financial performance in corporate acquisitions: BRICS evidence РЖМ 20 (1): 28-51 (2022) combine operations while economies of scope is likely to appear when both firms are in the same chain of supply combine operations .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…They compared the operating performance of the bidder companies before and after the acquisition and indicated that the operating cash flow performance for combined firms improved significantly after acquisitions (Rahman & Limmack, 2004) [7]. Vu investigated failed takeover efforts in search of new evidence about whether mergers add or subtract value for acquirers and targets two months before and after the bid (Vu & Cole, 2007) [8]. Evaluation of acquisitions occurring from 1989 to 1993 reveals that the raw EVA of the acquirer company declined significantly after acquisitions, caused by the industry factors (Yook, 2004) [9].…”
Section: Literature Reviewmentioning
confidence: 99%